Long-term bank lending and the transfer of aggregate risk - Michael Reiter; Leopold Zessner-Spitzenberg (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2020)
Long-term debt contracts transfer aggregate risk from borrowing firms to lending banks. When aggregate shocks increase the future default probability of firms, banks are not compensated for the default risk of existing contracts. If banks are highly leveraged, this can lead to financial instability with severe repercussions in the real economy. To study this mechanism quantitatively, we build a macroeconomic model of financial intermediation with long-term defaultable loan contracts and calibrate it to match aggregate firm and bank exposure to business cycle risks. Our model exhibits banking crises that closely resemble observed crisis episodes. We find that such crises do not arise in an economy with short-term debt. Our results on the role of long-term debt completely reverse if financial regulation is implemented to increase banks' risk bearing capacity. The financial sector is then well equipped to take on the aggregate risk, such that long-term lending stabilizes the business cycle by providing insurance to the corporate sector.
Keywords: E32; E43; E44; G01; G21; 330; Banking; Financial frictions; Maturity transformation